Feasibility Analysis of a Novel Production Method for Monolithic Integrated MEMS with Nanogaps - Hohnloser, Daniel; Schuklin, Dennis; Schmidt, Carsten; Kreitmaier, Michael; Blasini, Mario; Hagelauer, Amelie Marietta; Weigel, Robert (IEEE Sensors, 2016)
This paper analyses a novel production technique for the fabrication of microelectromechanical system (MEMS) with a gap in the scale of nanometer. The technology is based on a density-changing layer, which let a gap arise through the shrinkage of this layer. After the description of the technology, the requirements for monolithic integration and CMOS compatibility with respect to this technology are worked out. It has been discovered that there are several challenges to be overcome, especially to find a material composition which match the requirements will be important as well as to set up the process without affecting other CMOS device parameters. But if these challenges are solved the process will be suitable for various applications and enable to open up new markets.
elib2cris::1512001600,hohnloser2016
Keywords: MEMS; NEMS

Highly Integrated Low Power Photomultiplier Readout ASIC Comprising Fast ADC to Be Used in the Antarctic Ice - Schuklin, Dennis; Röber, Jürgen; Stadelmayer, Markus; Mai, Timo; Weigel, Robert; Hagelauer, Amelie Marietta (2019 IEEE 19th Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2019)
After the successful launch of IceCube, the work is currently concentrated the next generation neutrino observatory at South Pole, IceCube Gen2. The neutrino detection and post processing accuracy mostly relies on used electronic hardware. The proposed highly integrated, low power photomultiplier readout ASIC is designed for function in low temperatures of Antarctic. The microchip comprises an input pre-amplifier, a clock generator and an ADC with encoder logic featuring sampling rate of 500MHz, 6bit output accuracy with a smart extension of input related resolution up to 8bit in the area of interest. It achieves the same accuracy like a standard 8bit ADC architecture but with significantly less hardware overhead and power dissipation.<br

Smart Sensor Framework: A Pressure Sensor for Smart Home Applications - Lieske, Tobias; Schuklin, Dennis; Hohnloser, Daniel; Reichenbach, Marc; Pfundt, Benjamin; Fey, Dietmar; Weigel, Robert (1. E|HOME-CENTER SYMPOSIUM, 2016)

Systemkonzept eines autarken und intelligenten Miniatur-Sensors für Smart Home - Schuklin, Dennis; Hohnloser, Daniel; Lieske, Tobias; Reichenbach, Marc; Bänisch, Andreas; Pfundt, Benjamin; Röber, Jürgen; Weigel, Robert; Fey, Dietmar (VDE Kongress 2016: Internet der Dinge, 2016)
Trotz der erheblichen Fortschritte im Bereich Smart Home, stellt die Installation von Hunderten von Sensoren eine der größten Herausforderungen dar. Eine mögliche Lösung für dieses Problem ist die Integration aller Komponenten innerhalb einer integrierten Schaltung. Dieser Beitrag stellt ein Konzept für ein intelligentes Sensorsystem dar, welches die wichtigsten Sensoren für das intelligente Zuhause (wie z.B. Drucksensor, Gassensor, Temperatur-, oder Lichtsensor) auf einem Chip vereint. Dadurch wird das Messen von lokalen Temperaturen, Lichtverhältnissen, Drucks und sogar Luftqualität ermöglicht. Mit diesen umfassenden Informationen können lebensunterstützende Systeme, Einbruchsdetektion, automatisierte Klimaregelung und Beleuchtungssteuerung in Räumen und vieles mehr realisiert werden. Langfristiges Ziel dieser Arbeit ist die Entwicklung eines selbst organisierenden und autonomen Netzwerks von intelligenten Sensoren im Bereich Smart Home. Mit Abmessungen von wenigen Zentimetern, kann jeder Sensor nahezu überall angebracht werden, wie zum Beispiel an einem Fenster.
elib2cris::1512001600,shuklin2016
Keywords: Smart Home; Intelligent Sensor System; MEMS Sensor; Analog to Digital Converter; Digital Processing Unit